Room Temperature Wannier-Stark Effect in 2D Macroporous Silicon Structures with Nanocoatings - L. A. Karachevtseva; S. Ya. Kuchmii; K. P. Konin; O. O. Lytvynenko; A. L. Stroyuk (Хімія, фізика та технологія поверхні)
The IR light absorption oscillations in 2D macroporous silicon structures with microporous silicon, SiO2 nanocoatings, and ZnO nanocrystals have been studied at room temperature. Oscillations with giant amplitude are observed in the spectral ranges of absorption by surface levels on "silicon – nanocoating" boundary. The electro-optical effect has been considered within the strong electric field approximation due to resonance electron scattering on the surface impurity states with the difference between two resonance energies equal to the Wannier-Stark ladder. Resonant electron scattering gives rise to the resonances of the permittivity and a corresponding change in the absorption. In this case, the Wannier-Stark effect is realized as a result of large-time electron scattering as compared with the period of its oscillations in the strong electric field of illuminated "silicon – nanocoating" boundary.